Sikap Masyarakat Adat Bali terkait Putusan Pesamuhan Agung III Majelis Utama Desa Pakraman Propinsi Bali Tahun 2010 - Sukerti, Ni Nyoman; Krisnawati, I G. A. A. Ari; APHA, Journal Manager (Jurnal Hukum Adat Indonesia, 2018)
This study aims to assess the relevant customary law of inheritance Bali after holding the position of women The Great Congregation III The Main Assemblies Pakraman Village (MUDP) Bali Province in 2010. The problem: 1. What is the meaning of the decision MUDP in 2010 ?. 2. How public attitudes Balinese customary law related to the MUDP decision ?. The method used to achieve the objectives of this study are socio-legal research, beginning with normative research, and field research by interviewing methods, data analysis with qualitative method. The first problem, Result research shows that mean Court III MUDP The Assembly's decision in 2010 reflects the significance of gender equality in the field of inheritance law. The second problem, research shows disagree and agree. Who disagreed give reasons; MUDP verdict unfair position daughters as heirs, customary laws regulate heirs are descendants of men and sentana rajeg MUDP decision does not reflect the principle of proportionality. Who agreed to give reasons; MUDP decision puts girls in heir own right and fair, courageous erode the old customary law binding, is an extraordinary breakthrough and reflects the recognition of the right of girls to inherit.